2020
DOI: 10.14393/bj-v36n6a2020-48217
|View full text |Cite
|
Sign up to set email alerts
|

Sensory acceptance and physico-chemical composition of mixed minas frescal cheese

Abstract: Buffalo milk presents higher proteins and lipids concentration than cow milk, which provides a better yield in cheese-making production and products with considerable sensory approval. However, buffalo milk is not regularly available throughout the year due to different handling conditions. Thus, to guarantee the supply of buffalo milk dairy products during the year, the addition of bovine milk is an alternative. Therefore, this study aimed to test the effect of a buffalo and bovine milk mixture for the Minas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, little is known about the viability of adding inulin and L. plantarum in the technological processing of semi-hard and semicooked cheeses made from a mixture of milk from different species. In a previous study carried out by our group, we demonstrated that the mixture of both milk varieties, buffalo and cow milk, provided desirable sensory characteristics, facilitating the insertion of buffalo dairy products in the dairy industry and the diversification of the chain production (Rekowsky et al, 2020). Thus, this study aimed to develop a new Brazilian Coalho buffalo cheese made with cow milk (colocar a porcentagem) and the addition of inulin and L. plantarum, on physicochemical parameters and bacteria viability during 10 days of ripening period.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, little is known about the viability of adding inulin and L. plantarum in the technological processing of semi-hard and semicooked cheeses made from a mixture of milk from different species. In a previous study carried out by our group, we demonstrated that the mixture of both milk varieties, buffalo and cow milk, provided desirable sensory characteristics, facilitating the insertion of buffalo dairy products in the dairy industry and the diversification of the chain production (Rekowsky et al, 2020). Thus, this study aimed to develop a new Brazilian Coalho buffalo cheese made with cow milk (colocar a porcentagem) and the addition of inulin and L. plantarum, on physicochemical parameters and bacteria viability during 10 days of ripening period.…”
Section: Introductionmentioning
confidence: 95%
“…CTL -control Coalho cheese (without the addition of probiotic or prebiotic); PRO -potentially probiotic Coalho cheese (with L. plantarum); PRE -Potentially prebiotic Coalho cheese (with inulin); SYMpotentially symbiotic Coalho cheese (with L. plantarum and inulin). The buffalo and cow milk (55:45 ratio), previously mixed according to Rekowsky et al (2020), was pasteurized (65ºC/30min) and cooled to 38 °C. The ingredients used were non-probiotic mesophilic homofermentative starter culture of Lactococcus lactis subsp.…”
Section: Technological Cheese Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…As the production rate of buffalo milk increased worldwide due to its technological and nutritional properties, several studies were conducted on the use of buffalo milk in the production of various cow milk-derived cheeses, such as Cheddar and Emmental (Murtaza et al, 2017b;Murtaza et al, 2013, Ladkani and Srinivasan, 1990a, 1990b. For instance, Rekowsky et al (2020) investigated the use of buffalo milk in the production of Minas Frescal cheese, which is a Brazilian soft white cheese prepared from cow milk through the enzymatic coagulation of milk using rennet, with or without starter cultures. Studies have reported that the fat content and total solids in the cheese prepared from buffalo milk were slightly higher than those in bovine milk.…”
Section: Introductionmentioning
confidence: 99%